Impact of Study Time at Home on an Academic Performance: A Focus towards Math and Science Subjects in British Curriculum in Abu Dhabi - SOUHAIL ABD EL BAKI, SARA (2025)
The educational system in the UAE is continuously evolving, and the aspects that can influence students' academic performance have received significant attention from policymakers, researchers, teachers, and parents. In this context, the current study investigates the impact of home study time on students' academic performance. The study's research specifically emphasises Maths and Science subjects in the British curriculum in Dubai. The primary research question is: How does study time at home affect the academic performance of British Curriculum school students, specifically in Math and Science subjects? The researcher adopts a mixed method combining both qualitative and quantitative approaches. For quantitative data, the questionnaire responses were taken from 100 research participants (students) enrolled in a British curriculum school, aged 12 to 18 years. For qualitative data, the interviews are conducted with 20 parents, 20 teachers, and 10 private tutors. The findings reveal a strong alignment between quantitative and qualitative data and indicate that study time at home positively impacts students' academic performance in Math and Science subjects. It is concluded that consistent study time at home plays a significant role in students' academic performance.